2005
DOI: 10.1017/s0967199405003114
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the ubiquitin-proteasome pathway in rat oocyte activation

Abstract: The role of the ubiquitin-proteasome pathway (UPP) in mitosis is well known. However, its role in meiotic division is still poorly documented, especially in the activation of mammalian oocytes. In this study, the role of proteasome in the spontaneous and parthenogenetic activation of rat oocytes was investigated. We found that ALLN, an inhibitor of proteasome, when applied to metaphase II oocytes, inhibited spontaneous activation, blocked extrusion of the second polar body (PB) and caused the withdrawal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…cyclin B and securin) for degradation by the proteasome (Schmidt et al, 2005). The ubiquitin–proteasome pathway is involved in many aspects of mammalian oocyte meiotic progression, such as spindle assembly, metaphase‐to‐anaphase transitions and pronuclear formation (Huo et al, 2004, 2006), and essential functions of this pathway have been reported in rat oocyte maturation and activation (Josefsberg et al, 2000; Tan et al, 2005). Faithful progression of meiotic divisions relies on tight control of APC/C activity (reviewed in Pesin and Orr‐Weaver, 2008).…”
Section: Mechanisms Of Maintenance and Exit From Metaphase‐ii Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…cyclin B and securin) for degradation by the proteasome (Schmidt et al, 2005). The ubiquitin–proteasome pathway is involved in many aspects of mammalian oocyte meiotic progression, such as spindle assembly, metaphase‐to‐anaphase transitions and pronuclear formation (Huo et al, 2004, 2006), and essential functions of this pathway have been reported in rat oocyte maturation and activation (Josefsberg et al, 2000; Tan et al, 2005). Faithful progression of meiotic divisions relies on tight control of APC/C activity (reviewed in Pesin and Orr‐Weaver, 2008).…”
Section: Mechanisms Of Maintenance and Exit From Metaphase‐ii Arrestmentioning
confidence: 99%
“…Supplementation of culture medium with proteasome inhibitors prevents degradation of ubiquitinated proteins and progression of the cell cycle (Josefsberg et al, 2000; Tan et al, 2005). Proteasome inhibitors such as MG132 and ALNN are often used to maintain rat eggs at metaphase II (Zhou et al, 2003; Ito et al, 2005, 2007a,b; Tan et al, 2005; Mizumoto et al, 2008; Nakajima et al, 2008; Popova et al, 2009; Sterthaus et al, 2009; Mizumoto et al, 2010). The advantages of using MG132 in embryo manipulations are controversial (Gao et al, 2005).…”
Section: How Spontaneous Activation Can Be Controlledmentioning
confidence: 99%
“…While proteasome activity is regarded as widely conserved and ubiquitous, functional investigations have shown that proteasomes have a specific role in the reproduction biology of several models [35,42,47,49], particularly in the signals that trigger oocyte maturation [36][37][38][39][40]43]. In this study, we discovered that the vitellogenic ovaries exhibit significant proteasomal activity, and that the silencing of the essential 20S proteasome subunit Prosα6 causes reduced proteasomal activity, which ultimately leads to complete oogenesis arrest and reproduction ablation in the Chagas disease vector R. prolixus.…”
Section: Discussionmentioning
confidence: 99%
“…In the goldfish (Carassius auratus) it was demonstrated that modifications of proteasomal subunits occur during oogenesis and that these modifications may be involved in the regulation of oocyte maturation [36]. In the study models Xenopus laevis and mice, it has been extensively demonstrated that the UPS participates in oocyte meiotic maturation, activation, and fertilization [37][38][39][40][41][42][43], as well as degradation of maternal proteins during the maternal to zygotic transition [44,45]. In insects, functional studies were performed in the fruit fly Drosophila melanogaster and showed that physiological proteasome activity is required to ensure normal progression of oogenesis [46].…”
Section: Introductionmentioning
confidence: 99%
“…UPP is important for oocyte meiotic maturation, fertilization, and early embryonic mitosis and may play its roles by regulating cyclin B1 degradation and MAPK/p90 Rsk phosphorylation in pig (Huo et al 2004a;Sun et al 2004) and in mouse (Huo et al 2004b;Karabinova et al 2011;Tan et al 2005a). UPP is required for meiotic maturation of rat oocyte (Tan et al 2005b). In gold fish, cyclin B degradation is initiated by the ATPdependent and ubiquitin-independent proteolytic activity of 26S proteasome and then the cyclin to be ubiquitinated for further destruction by ubiquitin-dependent activity of the 26S proteasome that leads to MPF inactivation (Tokumoto et al 1997).…”
Section: Ubiquitin-proteasome Pathwaymentioning
confidence: 99%